Making Visible New Learning: Professional Development with Open Digital Badge Pathways - Erin Fields (Partnership: The Canadian Journal of Library and Information Practice and Research, 2015)
Emerging fields of study and technological developments have provided the library profession with new opportunities to shift the role of the library and librarian. This shift, while exciting for its possibilities, complicates professional development when an attempt is made to build expertise in areas without structured learning paths as found in formalized education. This article addresses possible ways the profession can give clarity and purpose to our own educational and career growth while building a collaborative and diverse learning program through open digital badges.